Environmental Awareness of Biology Education Students Through Social Media: Addressing Local Issues - Sari, Defita Permata; Febriana, Harlis; Anisia, Ica Wandari; Suprayogi, Dawam (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
Environmental degradation caused by illegal mining, deforestation, forest fires, and poor waste management, represents not only an environmental crisis but also a critical educational issue. These conditions indicate a low level of environmental awareness, emphasizing the urgency of cultivating ecological responsibility among prospective teachers. As future educators, they play a strategic role in integrating environmental values into learning processes to promote sustainable attitudes and behaviors among students. This study aims to assess the environmental awareness profile of biology education students, using social media to contextualize local ecological issues. A quantitative descriptive design was applied to 78 purposively selected students who had completed the conservation biology course. Data were collected using a validated 35 item questionnaire based on the New Ecological Paradigm (NEP) scale, covering five dimensions: limits to growth, anti-anthropocentrism, fragility of nature’s balance, rejection of exceptionalism, and possibility of an ecocrisis. Results show that overall environmental awareness was in the good category, with the highest scores in fragility of nature’s balance and possibility of ecocrisis, and the lowest in rejection of exceptionalism. This study concludes that biology education students demonstrated a good level of environmental awareness across the five dimensions of the NEP. These findings indicate that prospective biology teachers possess a relatively strong ecological perspective, which may support their future role in promoting environmental responsibility in schools. Future environmental education initiatives may benefit from integrating social media as a contextual platform for presenting local environmental issues and strengthening students' engagement with ecological challenges.